3)-5-(-2 1/3); 4)-8-(-1-7);

vysochina67 vysochina67    3   27.10.2020 11:18    0

Ответы
Juliaghkfhcuf Juliaghkfhcuf  26.11.2020 11:18

Пошаговое объяснение:

3).

- 5 - ( - 2 \frac{1}{3} ) = - 5 + 2 \frac{1}{3} = - 2 \frac{2}{3}

4).

- 8 - ( - \frac{1}{7}) = - 8 + \frac{1}{7} = - 7 \frac{6}{7}

ПОКАЗАТЬ ОТВЕТЫ
Elizabeth1006 Elizabeth1006  26.11.2020 11:18

3).

- 5 - ( - 2 \frac{1}{3} ) = - 5 + 2 \frac{1}{3} = - 2 \frac{2}{3}−5−(−2

3

1

)=−5+2

3

1

=−2

3

2

4).

- 8 - ( - \frac{1}{7}) = - 8 + \frac{1}{7} = - 7 \frac{6}{7}−8−(−

7

1

)=−8+

7

1

=−7

7

6

Пошаговое объяснение:

бери

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика